Muffler design optimization through experimental analysis of noise and back pressure - Mohiuddin, A. K. M.; Ideres, Mohd Rashidin; Mohd Hashim, Shukri (2005)
Exhaust noise of internal combustion engines is known to be the biggest pollutant of the presentday urban environment. The main objective of this paper is to find the relationship between the back pressure and the noise level. Back pressure represents the extra static pressure exerted by the muffler on the engine through restrictions in the flow of exhaust gases. This needs to be kept to a minimum. The relationship between the noise and the back pressure is inversely proportional; lowering the noise level at the tip will result in high back pressure. However, this relationship is undesirable as the requirement is to have a quiet muffler with a small back pressure (ideal muffler). The design of the muffler chamber separation and arrangement is essential in determining the muffler characteristics. Some design considerations are proposed in order to come up with an optimum muffler design. The experimental data show a general shape of an average design of the muffler which would be the mostsuitable for the test car model.